#TITLE_ALTERNATIVE# - MARTINA (NIM : 10106047); Pembimbing Tugas Akhir: Prof. Dr. Sutawanir Darwis, ANNISA
Reservoir is the place of oil acumulation. Currently, oil has an important role in human life. Because the amount of oil availability is limited in nature and amount of effort and cost in producing are expensive, it needs a method that can optimize the oil production process. The condition of reservoir can affect to oil production. Thus required a model that can give an exact picture of the actual reservoir conditions. The model needs a method of updating or parameter estimation of reservoir. One method of estimation for reservoir parameters is the history matching, it carried out the alignment process reservoir performance of the simulation results with actual conditions. This final project describes how to apply of Ensemble Kalman Filter (EnKF) which is the development of Bayesian principles, in the history matching is used to update the parameters in the reservoir. EnKF used to assimilate the new production data (static and dynamic) which will be used to correct the model. Based on the assimilating production data process, EnKF corrects the reservoir permeability model. Static data obtained from a source and dynamic data from analytic solution.